Mental health disorders in child and adolescent survivors of post-war landmine explosions. Issue 1 (December 2015) - Hemmati, Mohammad; Shokoohi, Hamid; Masoumi, Mehdi; Khateri, Shahriar; Soroush, Mohammadreza; Modirian, Ehsan; Poor Zamany Nejat Kermany, Mahtab; Hosseini, Maryam; Mousavi, Batool
Abstract Background To describe the mental health status of 78 child and adolescent survivors of post-war landmine explosions. Methods Child and adolescent survivors of landmine explosions who were younger than 18 years old at the time of the study were identified and enrolled in this study. The mental health status of the participants was assessed by general health assessment and psychiatric examinations. Psychiatric assessment and diagnosis were undertaken using the Diagnostic and Statistical Manual for mental disorders (DSM-IV) criteria. A psychiatrist visited and interviewed each survivor and identified psychiatric disorders. Results Seventy-eight child and adolescent survivors with a mean age of 16.11 ± 2 years old were identified and agreed to participate in the study. The mean age of the victims at the time of injury was 8.2 ± 3.12 years old (range 2–15). Thirty-seven (47.4 %) of the adolescent survivors suffered from at least one psychiatric disorder. Twenty-nine survivors (37.1 %) were newly diagnosed and needed to start medication and psychiatric treatment. The most common findings were anxiety disorders (34.6 %), including posttraumatic stress disorder (PTSD) in 20 (25.6 %), and generalized anxiety disorder (GAD) in 7 (9 %) subjects. Mild-Moderate depression was found in 5 (6.4 %) subjects. No personality disorders were observed, and two patients suffered from mental retardation. The study results revealed a significant association between age of casualty, duration of injury and limb amputation, and types of psychological disorders. Conclusion Child and adolescent survivors of landmine explosions had a high prevalence of psychiatric disorders.